General movement optimality score and general movements trajectories following early parent-administrated physiotherapy in the neonatal intensive care unit. (December 2021) - Ustad, Tordis; Fjørtoft, Toril; Øberg, Gunn Kristin
Abstract: Background: The Prechtl General Movement Assessment (GMA) is a reliable tool for the functional assessment of the young nervous system. It is based on a global assessment of the quality of infants' movements. In addition, detailed steps of assessment have been developed – one for preterm and term age, and one for use between 3 and 5 months. One potential benefit of such a detailed analysis is the documentation of subtle changes in the infants' spontaneous movements caused by early intervention. Aim: To present detailed scores of the infants' general movements (GMs) at preterm age, and of the infants' motor repertoire at 3 months' postterm age (PTA), for infants having participated in a randomized controlled trial (RCT) of early intervention, and to examine possible group differences. In addition, the aim is also to present the GMA from preterm to 3 months' PTA, comparing the intervention and the control group. Study design: A retrospective study on infants who had participated in an RCT of parent-administered early intervention. Subjects: 141 infants born very preterm. Outcome measures: GMA, "Detailed Assessment of General Movements During Preterm and Term Age" and "Assessment of Motor Repertoire at 3 to 5 months". Results: The GMA and the detailed assessments of GMs conducted at 36 weeks' post menstrual age (PMA) showed the same distribution of normal and abnormal movements in both the intervention and in the control group, as did the assessment of motor repertoire at 3 months' PTA. Conclusion: Neither the GMA nor the detailed assessments of GMs at 36 weeks' PMA and of the motor repertoire at 13 weeks' PTA suggest that early intervention, performed before term, changes the GMs of very preterm-born infants. Highlights: Parent-administrated physiotherapy in the NICU had no noticeable effect on the global GMs of preterm-born infants. A detailed analysis of GMs during preterm age revealed no subtle, early-intervention-related changes in movements. Only in very few infants did the GMs normalize during preterm age.